2005
DOI: 10.1089/bsp.2005.3.331
|View full text |Cite
|
Sign up to set email alerts
|

The Willingness of U.S. Emergency Medical Technicians to Respond to Terrorist Incidents

Abstract: A nationally representative sample of basic and paramedic emergency medical service providers in the United States was surveyed to assess their willingness to respond to terrorist incidents. EMT's were appreciably (9-13%) less willing than able to respond to such potential terrorist-related incidents as smallpox outbreaks, chemical attacks, or radioactive dirty bombs (p<0.0001). EMTs who had received terrorism-related continuing medical education within the previous 2 years were twice as likely (OR=1.9, 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
105
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 10 publications
9
105
0
Order By: Relevance
“…However, recent evidence indicates that this worker population may not always feel prepared, or willing, to respond to such incidents. [2][3][4] Their reluctance could undermine the ability of the healthcare system to meet surge capacity needs anticipated for incidents of this kind. 5 A recent nationally representative sample of paramedics showed that concern about infection or contamination predicted significantly lower response willingness, compared to natural disasters such as earthquakes or floods.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, recent evidence indicates that this worker population may not always feel prepared, or willing, to respond to such incidents. [2][3][4] Their reluctance could undermine the ability of the healthcare system to meet surge capacity needs anticipated for incidents of this kind. 5 A recent nationally representative sample of paramedics showed that concern about infection or contamination predicted significantly lower response willingness, compared to natural disasters such as earthquakes or floods.…”
mentioning
confidence: 99%
“…5 A recent nationally representative sample of paramedics showed that concern about infection or contamination predicted significantly lower response willingness, compared to natural disasters such as earthquakes or floods. 2 Medical staff surveyed about their willingness to work in field hospitals during mass casualty incidents were less willing to do so if CBRNE agents were involved. 6 Perceived risk, knowledge of the operating environment, and self-assessed capacity to provide the care required were the factors that most strongly affected willingness to work in such environments.…”
mentioning
confidence: 99%
See 3 more Smart Citations